HOUDINI AMONG THE SPIRITS: A LESSON IN CRITICAL THINKING. Issue 52 (4th June 2019) - Guzzo, Guilherme Brambatti
Abstract : In spite of the widespread recognition of critical thinking as an elementary aim of education, and an important tool for people to evaluate information and make reasonable decisions in their daily lives, to think critically is a difficult task. We are consciously and unconsciously biased, and our basic beliefs strongly influence the way we assess evidence, so our cognitive default condition seems to move us away from critical thinking. However, it is possible appropriately to exercise critical thinking to evaluate subjects to which we are emotionally attached, and the experience of the illusionist Harry Houdini investigating Spiritualism is a striking example of it. My objective here is to discuss how Houdini incorporated core elements of critical thinking, such as the ability to evaluate reasons, and the disposition to calibrate his beliefs accordingly, in his assessment of the claim that Spiritualist mediums could contact the spirits of dead people, as described in his book A Magician among the Spirits .